The changing resistance patterns of bacterial uropathogens in children. Issue 9 (30th September 2020) - Kurt‐Şükür, Eda Didem; Özçakar, Zeynep Birsin; Doğan, Özlem; Öztürk, Musa; Karaman, Merve; Çakar, Nilgün; Güriz, Haluk; Yalçınkaya, Fatoş
Abstract: Background: Increased antimicrobial resistance is a problem in managing urinary tract infections (UTI). With this study we assessed the resistance patterns of urinary isolates in children with UTI between January 2017 and January 2018. Methods: A retrospective cohort study was conducted. Among 5, 443 isolates, a total of 776 UTI episodes in 698 patients were included. Patients' gender, age, voiding dysfunction, UTI history, prophylaxis status, and presence of vesicoureteral reflux were noted. Patients were divided into three age groups: group 1 for ages ≤12 months; group 2 for ages 13–60 months; and group 3 for ages >60 months. The susceptibilities of etiologic agents to different antimicrobials were explored. Results: Median age was 54 months (range 1 month–21 years); male to female ratio was 1:5. The most common causative agent was Escherichia coli (83% of the cases), followed by Klebsiella pneumoniae (7.5%). Resistance to ampicillin (62.6%) and co‐trimoxazole (39.8%) were remarkable in all isolates. Overall extended‐spectrum beta‐lactamase (ESBL) positivity was 23.5%. The highest resistance rates, higher ESBL positivity (28.6%), and K. pneumoniae frequency (13.5%) were observed in group 1. Ceftriaxone resistance was significantly low (0.5%) in the ESBL (−) group, which constituted the majority of the isolates. Higher resistance rates were observed among the patients on prophylaxis compared to those off prophylaxis ( P < 0.001). Conclusion: Ceftriaxone can still be used for empirical treatment; however, initial urine culture results are crucial due to high ESBL positivity. Special consideration must be taken for patients under 1 year of age. Periodical surveillance studies are needed to explore the changing resistance patterns of uropathogens and modify treatment plans.